Multiple Orientation Circuits Converging on the Pd7 Cells in Tritonia diomedea. (13th June 2012) - Abraçado, L. G.
Abstract : Magnetoreception is a sophisticated orientation mechanism, involving a magnetoreceptor connected to the nervous system with signal amplification. The mollusk Tritonia diomedea is a good model to investigate the behavioral and neural responses to the magnetic field. The mollusk inhibits all unnecessary activities and focuses on an available cue during orientation. Although Pd7 cells are inhibited by magnetic pathway, it was excited by another stimulus, water streams plus food odor. Two sensory pathways connected to Pd7 through the same or different circuits were tested. The action potential activity through Pd7 was compared in these different stimulations. The changes in Pd7 activity indicate a response of enhanced electrical activity to water streams plus food odor stimulus, and Pd7 activity can be excited by at least one of these stimuli. These results indicate an inverse relationship between magnetic orientation and feeding.